(3CeGdj GdbGdjs - (3CHh Ydj GdbGdj , ESeGYjd Hf GdbGSe Hf YHOhf Hf gGQhf Hf YjSi Hf eMeO Hf SdeGf, CHh Ydj,J (B356 (3g` s
(3ChdgG (B:s
(3CeG HYO(B: (3aEffj deG QCjJ GdYde CfaS HVGYI, hCjbfJ Cf WdHg CaVd JLGQI, aGZJQHJ ddQhGjI hdReJ GdYdeGA ddOQGjI aCeddJ gPG GdcJGH ef MaXj s
(3BNQgG (B:s
(3bGd Gddg YR hLd(B: "(3CcGO oCNajgG(B" (3hgj bQGAI GdYGeI hGdfGS hQhi Yf SYjO Hf oLHjQ Cfg cGf jbQC CcGO (B((3CNajgG HaJM GdgeRI(B) s
(3bWYI ef fSNI QGHYIs
(3JHUQI GdYfhGf (B:s
(3TQM hGedGA s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B64 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B165s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs